السرقة والقتل الأسري في مصر خلال العصر البطلمي: دوافعها ومعدلاتها وآثارها - دياب، أحمد فاروق رضوان (جامعة المنوفية - كلية الآداب, 2020)
يبدو أن أغلب جرائم القتل في مصر خلال العصر البطلمي كان سببها السرقة، ولم تكن هذه الجرائم مستحدثة عندئذ، بل كانت متأصلة منذ قديم الأزل. ونظرا لأن مفهوم القتل بصفة عامة-سواء داخل الأسرة أو خارجها-كان هو الاعتداء على أشخاص الناس وأرواحهم، فمن ثم تعد هذه جريمة في حق المجتمع كافة. لذا أعد لها المشرع قانونا جنائيا صارما، يعاقب كل من يرتكب هذه الجرائم؛ سواء السرقة أو القتل داخل الأسرة أو خارجها. ولم تقتصر جرائم السرقة والقتل الأسري على الرجال فقط، بل شملت النساء أيضا، وكذلك شملت الأبناء الصغار، وكان يطلق عليهم الحدث Παρπηωμαηιτόι، كما لم تقتصر على طبقة بعينها، بل شملت جميع الطبقات؛ سواء الحاكمة، أو المحكومة أيا كانت؛ أرستقراطية، أو كادحة. لقد كان المجني عليهم في هذه القضايا يلجؤون إلى المحاكم لينالوا حقوقهم، وكانت المحاكم ثلاث فئات؛ محاكم للإغريق، ومحاكم للمصريين، ومحاكم للأجانب، وكان بعض ملوك البطالمة يعفون رعاياهم-أحيانا-من عقوبة بعض الجرائم، ما عدا جريمة القتل العمد؛ نظرا لعظمتها. أما جريمة السرقة فتنوعت المصطلحات المعبرة عنها (ἀφαιρεῖν-κλείπεινἀ-φαρπάζειν)، وذلك ربما لارتباطها بنوع الجريمة، وكيفيتها، والظروف التي ارتكبت فيها، والعقوبات المرتبطة بها، وتنوعت المسروقات فيما بين الأموال والممتلكات المنقولة والثابتة، وكان القانون يعاقب مرتكبيها؛ لأنهم تسببوا في الإضرار بممتلكات الغير. ولم تقتصر جرائم السرقة والقتل الأسري على الزوج والزوجة والأبناء فقط، بل شملت الأقارب أيضا داخل العائلة، والخدم أحيانا داخل الأسرة، وإن كنا نحتسبها جرائم أسرية غير مباشرة. ولم يكن الباحث هو الأوحد في عرض الجرائم بصفة عامة، بل سبقه كثير من الدراسات إلا أننا عرضنا الجرائم الأسرية من خلال البحث نظرا لعظمتها داخل المجتمع، ودور الدولة في القضاء عليها، من خلال تشريعات القوانين التي ربما تجبر الجاني في عدم ارتكابه لجريمته الأسرية وبذلك تكون الدولة قد قامت بدورها في القضاء على هذه الظاهرة التي تهدد المجتمع كافة. ومن ثم تم عرض نماذج لجرائم السرقة والقتل الأسري في مصر في العصر البطلمي ودور الدولة في معاقبة الجاني واسترداد حق المجني عليه من خلال المصادر المختلفة.
It appears that most of the murders were caused by theft, and these crimes were not introduced in Egypt during the Ptolemaic era, but were known from ancient times, and the concept of killing in general – whether inside or outside the family - was to attack people and their lives, and then it is considered A crime against all society. so the legislator prepared for her a strict criminal law, which punishes those who commit these crimes, whether theft, or killing inside or outside the family, and the crimes of theft and family killing were not limited to men only, but also included women, and also included young children, And the event was called Παρπτωματιχόι, as it was not limited to the layer of Ba It was forbidden, but included all classes, whether the ruling, or the ruled, whatever it was; aristocratic or industrious. In these cases, the victims resorted to the courts to obtain their rights, and the courts were of three categories; Courts of the Greeks, courts of Egyptians, and courts of foreigners, and some Ptolemaic kings sometimes exempted their subjects from the punishment of some crimes, except for the crime of premeditated murder; Because of its greatness. As for the crime of theft, the expressions varied (ἀφαιρεῖν-κλείπεινἀ- φαρπάζειν). This may be related to the type of crime, how it was committed, the circumstances in which it was committed, the penalties associated with it, the diversity of theft between money and movable and Immovable property, and the law punished the perpetrators; because they Have caused damage to the property of others. Theft and family killings were not only limited to the husband, wife and children, but also included relatives within the family, and sometimes servants within the family, although we consider it indirect family crimes. The researcher was not the only one to present crimes in general, but was preceded by many studies, but we offered family crimes through research due to their greatness within society, and the role of the state in eliminating them, through legislation laws that might compel the perpetrator not to commit his family crime and thus be The state has played its part in eliminating this phenomenon, which threatens all society. Then, examples of the crimes of theft and family killing in Egypt in the Ptolemaic era and the state's role in punishing the perpetrator and restoring the victim's right through various sources were presented.
Keywords: العصر البطلمي -- مصر تاريخ -- جرائم السرقة